Exostosis Bursata: A Not to be Forgotten Differential for Cystic Periscapular Swelling - Rana, Alisha; Verma, Mansi; Aggarwal, Neeti; Tomar, Ashwani; Aggarwal, Vineet (Journal of the Association of Physicians of India, 2025)
Bursa formation in association with osteochondroma is rarely reported in the literature. We hereby present a case of a 23-year-old female who had a cystic periscapular swelling and a multimodality approach for establishing the diagnosis.